(untitled) (Bheshaja: Journal of Central Ayurveda Campus, 2025)
Background: Community Health Score Board is a monitoring and evaluation tool that enables service users to assess and rate the performance of services provided by the service providers using a grading system in the form of scores. It is included under the nine accountability and integrity tools of 21 social accountability tool developed by World Bank. It is implemented in Different Village Development Committees of Kailali, Doti and Dadeldhura districts. Objectives: Assessing the effectiveness of Community Health Score Board in utilization of maternal health services. Methods: This study used the quasi-experimental technique to evaluate the impact of Community Health Score Board (CHSB) on maternal health in Far Western Nepal. Study area was classified into the intervention group and the control group. VDCs where the program was implemented until the study were classified as intervention group and the rest were classified as control group. VDCs were randomly selected to avoid the possible selection bias. Both quantitative and qualitative research methods were used for study. Primary data was collected by Focus Group Discussion, In Depth Interview, Key Informant Interview and secondary data was collected from Health Management Information System records of health facilities in May-June 2013. Data analysis was done by using SPSS 16 and Epi Info version 7stat calc-6 after the entry in Epi Data-3.1 in different stages. The collected data grouped under PHCC category, HP category and SHP categories were tabulated in tables then Chi-square test was applied to find the statistical association among base line and end line data of intervention and control groups. Results: Due to Community Health Score Board, knowledge, attitude and practice of mothers towards Maternal Health services were changed; their health seeking behavior was improved. Health Workers started to work devotedly for better response in community evaluation. Conclusion: This study showed that Community Health Score Board is an important monitoring and evaluation tool to make the health workers and community people accountable to their rights and responsibilities. It brought positive impact on knowledge, attitude and practice of mothers regarding use of maternal health services. More pregnant mothers used to visit ANC clinics for pregnancy checkups and attracted to institutional delivery. Similarly it changed the attitude of health workers towards their duty. They became devoted and responsible to community with showing politeness and respect to service users. Moreover it raised feeling of community ownership of local people towards health facilities.